Guiding the use of collective feedback displayed on heatmaps to reduce group conformity and improve learning in Peer Instruction. - Michinov, Nicolas; Anquetil, Éric; Michinov, Estelle (Journal of Computer Assisted Learning, 2020)
Peer Instruction is an active learning method widely used in higher education, whereby students answer a series of questions twice, once before and once after peer discussion. There is an ongoing debate as to whether a collective feedback should be given after the students' initial answer, and if so, how the frequently observed group conformity can be avoided. This study examined whether guiding on the use of this feedback can reduce group conformity and improve learning using an interactive learning environment to administer a new type of quiz using graphics, and delivering collective feedback to the whole class in a novel heatmap format. In the experimental group, the teacher told the students that the answer indicated by the heatmap was not necessarily the correct one; this information was not given to students in the control group. Results revealed that guided students were less likely to adopt the (incorrect) majority answer than the non‐guided students, and consequently, they were more likely to improve their learning by reaching an agreement about the correct answer through discussion with their peers. These findings suggest that guiding students in their use of collective feedback may have a crucial role in Peer Instruction.